Pemetaan Komoditas Basis di Kecamatan Polongbangkeng Utara Kabupaten Takalar - Muhammad Anshar; Irsyadi Siradjuddin (Diponegoro University, 2021)
The policy for commodity development in Polongbakeng Utara District has not been able to optimize its natural resource potential. One of the efforts to optimize this potential is the identification of food crops basis commodities by potential mapping in each village in Polongbangkeng Utara District. This study aims to identify the food crops commodity which is a basis commodity and to make the basis commodities mapping in Polongbangkeng Utara District. The analytical method used is LQ analysis and Ar-GIS mapping. The results showed that the food crops commodities which were the basis commodities in Polongbangkeng Utara District were rice, corn, green beans, cassava and sweet potatoes. Palleko is a village that has the most basis commodities with 4 basis commodities, namely rice, green beans, cassava and sweet potato. Rice and sweet potato commodities are the most basis commodities because they are the basis for 12 villages out of 18 villages in Polongbangkeng Utara district. Base commodity mapping was carried out on 5 food crop commodities. Mapping results show that there are more non-basis commodity polygons (50 polygons) than basis commodity polygons (40 polygons).